A potential low cost medium for cultivation of Dunaliella salina DCCBC15 in Vietnam - Duc, Tran Ngoc; Nhu Nguyen, Doan Thi; Quang Minh, Ho Ky; My Lan, Nguyen Thi; Portilla, Sixto; Tung, Hoang; Tien, Duong Duc (Academia Journal of Biology, 2013)
Dunaliella salina is a marine alga with high potential for beta-carotene (pro-vitamin A), up to more than 10% of cellular dry weight under appropriate stress conditions of limiting one of the following nutrients: nitrogen, phosphate, high light or high salt. Obtaining high biomass in low cost medium is the essential step of the two-phase culture system for beta-carotene production. For future development of beta-carotene production from Dunaliella in Vietnam, it is our first step to study a low cost medium using natural seawater enriched with industrial fertilizer N-P-K (30-15-10) commercially available in Vietnam. The primary results of biomass, cell density, chlorophyll a as well as growth rate are very promising to use this medium for mass culture of Dunaliella salina. The medium is recommended for growing other marine algae as well.